SENSORY GARDEN ACTIVITIES: A WELL-BEING PROGRAM FOR ELDERLY WITH RISK OF DEMENTIA IN WONOREJO URBAN VILLAGE, SURABAYA - Gayatri, Putu Angita; Soegiharto, Annisa Putri; Adisti, Shafira Tri; Pratiwi, Dida Amanda; Paramita, Pramesti Pradna (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
This article discusses a community service initiative in partnership with the Sapto Argo Elderly Community Health Post in Wonorejo District, Surabaya, targeting 17 elderly individuals at risk of dementia who enjoy gardening. Conducted from August to September 2023, this program introduced a recreational therapy-based sensory garden activity. Given that mental health programs focusing on elderly well-being are rarely implemented, this activity aimed to address that gap. Evaluation used a one-group posttest-only design, incorporating interviews and observations, and followed the Bradford Well-Being Profile to assess elderly well-being indicators. The evaluation revealed that the sensory garden activities had a positive impact on participants' well-being, enhancing their sense of purpose, positive emotions, and social interactions. Overall, the program successfully supported the mental health of the elderly at risk of dementia through meaningful and engaging activities.